The Role of Information Concerning the Arbitrator’s Preferences - Bruce, Christopher (Relations industrielles / Industrial Relations, 1981)
The purpose of this paper is to propose to extend the theoretical literature on bargaining under arbitration by categorising arbitration Systems not only by the type of selection procedure employed but also by the amount of information conveyed to the parties about the preference function of the arbitrator.